2022
DOI: 10.1016/j.heliyon.2022.e08792
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitude and academic achievement in a flipped classroom

Abstract: A quasi non-equivalent, non-randomized factorial design, examined Chemistry students' attitudes towards chemistry and academic achievement in second year Bachelor of Education students taught with the flipped classroom strategy. In the study of 100 students, a pre-attitude test of 30-items questionnaire was apportioned to ascertained students' attitude towards chemistry. Pre-test was also apportioned to the control and experimental group. This was followed by teaching using the flipped classroom strategy for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
(35 reference statements)
0
14
0
1
Order By: Relevance
“…Meanwhile, SAA was significantly affected by the Students’ Performance Response (β: 0.754; p = 0.014). It implies that a positive performance can give positive results in student’s academic achievement, and that a negative performance can also give negative results [ 64 ]. Pekrun et al (2010) discovered that students’ academic emotions are linked to their performance, academic achievement, personality, and classroom circumstances [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, SAA was significantly affected by the Students’ Performance Response (β: 0.754; p = 0.014). It implies that a positive performance can give positive results in student’s academic achievement, and that a negative performance can also give negative results [ 64 ]. Pekrun et al (2010) discovered that students’ academic emotions are linked to their performance, academic achievement, personality, and classroom circumstances [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Bossman & Agyei (2022), satisfaction significantly affects performance or learning outcomes [ 68 ]. In addition, it was discovered that the main drivers of the students’ performance are the students’ satisfaction [ 64 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The evidence showed a positive and significant correlation between teachers’ teaching experience and their empathic concern, from which it can be argued that general life experience among teachers and parents positively influences the empathetic level. Although junior teachers add new energy to teaching ( Nja et al, 2022 ), they may hardly put themselves in a victim’s shoes and perceive the problem as the victim does. Young teachers’ perspectives and feelings toward the victims of risky behaviors (i.e., early sex debut and early pregnancy) are yet to the level of their senior teachers’ counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…This was evidenced by the statistical analysis, which confirmed that micro-flipped learning had a positive and broadly significant effect on academic achievement. As a matter of fact, in the bulk of literature, many studies (Polat & Karabatak, 2022;Nourinezhad, Hadipourfard & Baval, 2022;Jdaitawi, Hussein, Muhaidat & Joudeh, 2022;Bergeson, 2022;Nja, Orim, Neji, Ukwetang, Uwe & Ideba, 2021;Masadeh, 2021;Hava, 2021) which highlight that flipped learning positively affects academic achievement. In this case, it can be presumed that the finding of the study goes in line with the relevant literature and that the abovementioned approach positively influences the learning achievement of the postgraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from several studies suggest that there are positive effects of flipped learning in the field of education (Polat & Karabatak, 2022;Nourinezhad, Hadipourfard & Baval, 2022;Jdaitawi, Hussein, Muhaidat, & Joudeh, 2022;Bergeson, 2022;Nja, Orim, Neji, Ukwetang, Uwe, & Ideba, 2021;Masadeh, 2021;Hava, 2021). By contrast, other studies have also emphasized the lack of any significant increase in learning performance (Arriaga & Talavera, 2018;Topal & Akhisar, 2018;Aggarwal, Thakur, Agrawal, Jhajharia, Madaan & Mahapatra, 2019;Leatherman & Cleveland, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%